SYNCHRONIZATION OF ENGLISH STUDENTSâ€™ WORKSHEET (LKS) TO THE CURRICULUM - Neneng Heni Nurhidayah; Farouk Imam Arrasyid (IAIN Syekh Nurjati Cirebon, 2017)
Abstract: This analysis is intended to uncover the synchronization between the studentsâ€™ worksheet for vocational high school to the School Based Curriculum. This research explores the profile of the English studentsâ€™ worksheet; evaluate the synchronization between the English studentsâ€™ worksheetâ€™s content and assessment to the learning objective in curriculum. This research utilizes qualitative research design, particularly in the form of a descriptive-evaluative content analysis. The data collection technique is in non-participant analysis study. The primary data is one printed studentsâ€™ worksheet entitled â€œBAHASA INGGRIS Untuk SMK TEKNIKâ€ published by MARGA MITRA and is used in SMK Al-Hidayah Cirebon. The data are analyzed by using textbook evaluation checklists which are represented into percentage and described into paragraph description as the result. The result of the research shows that the analyzed studentsâ€™ worksheet obtains over a third of poor items, nearly two third of good items , and only a small portion of excellent. It means that this studentsâ€™ worksheet is mostly categorized good in the term of general evaluation. However, fact found that some contents and assessments in this studentsâ€™ worksheet are out of the guidance in the syllabus. It is clear that it contains roughly a quarter of not synchronous assessment in speaking, nearly a third in reading, and nearly two third in writing. It indicates that the references and the guidance of the studentsâ€™ worksheet are questionable and untrustworthyKeywords: Studentsâ€™ Worksheet, Synchronization, Curriculum, Syllabus, Learning Objective.